The Cordilleran Ice Sheet and the Glacial Geomorphology of Southern and Central British Colombia - Ryder, June; Fulton, Robert; Clague, John (Géographie physique et Quaternaire, 1991)
ABSTRACTThis paper reviews the current state of knowledge about the Cordilleran Ice Sheet in southern and central British Columbia. Reconstructions of the ice sheet and the styles of ice expansion and déglaciation are based on extensive and varied glacigenic sediments and landforms that date from Late Wisconsinan (Fraser) Glaciation. Late-glacial lakes and sea level changes are also described and related to isostatic and eustatic effects. The timing of ice expansion and recession during Fraser Glaciation was markedly asymmetric: ice build-up commenced about 29 000 years BP, culminated between 14 500 and 14 000 years BP1 and déglaciation was largely completed by 11 500 years BP. Most of this interval appears to have been dominated by montane glaciation, which produced striking erosional landforms. A Cordilleran Ice Sheet existed from only about 19 000 to 13 500 years BP. An older glaciation, probably of Early Wisconsinan age, has been recognized from widespread exposures of drift that underlies Middle Wisconsinan non-glacial sediments. Pre-Wisconsinan drift is present near Vancouver. Drifts of late Tertiary to Middle Pleistocene age have been dated by association with volcanic sequences in the southern Coast Mountains and the central Interior, and by paleomagnetic studies in the southern Interior.